Dell Inc. : managing reputation in the blogosphere (B) - Pulscher, Shawn, (SAGE Knowledge. Cases., 2017)
After deeming Dell's customer service unsatisfactory, Jeff Jarvis, a well-known Internet blogger, posted an extremely critical open letter to the company's CEO. Within a matter of days, Dell had a full-blown crisis on its hands and was forced to reconsider how to deal with emerging technological platforms used by customers to communicate information and opinions.